Smart Guard Home Berbasis Internet Of Things - Sopiyan, Sopiyan; Selina, Selina; Yulianto, Andik (Universitas Internasional Batam, 2023)
Smart Guard Home is a design for security, safety, comfort and prevention for humans. Internet of Think-Based Smart Guard Home which the author designed uses an interconnected Microcontroller and Sensor which is then sent over the network to a PHP (Hypertext Preprocessor) Web server which is responsible for sending data via the HTTP (Hypertext Transfer Protocol) protocol and running scripts. Appropriate PHP. PHP scripts are used to process requests, access databases, and generate dynamic content which will be sent to the Database which is then sent back to the client. The author uses the hosting MySql Database which is then accessed using CPanel and managed using PHP Scrip and sent via the internet to the Android application. Mobile and web applications are Android UI/UX-based applications for real-time monitoring and notifications that can be accessed anywhere and anytime via the internet network.